An Improved Best Estimate Plus Uncertainty Method for Small-Break Loss-of-Coolant Accident in Pressurized Water Reactor - Sun, Dabin; Zhang, Zhijian; Li, Xinyu; Li, Lei; Wang, He; Xu, Anqi; Chen, Sijuan (Frontiers in Energy Research, 2020)
Best estimate plus uncertainty (BEPU) analysis method has been widely used to analyze various transient accidents of pressurized water reactor (PWR). However, the traditional BEPU method has some limitations: (1) The input parameters are not clearly defined, resulting in inaccurate conclusions in the sensitivity analysis. (2) The uncertainty quantification and sensitivity analysis usually share the same set of samples, but they have different requirements for the sample size. In this work, an improved BEPU method is proposed, which can alleviate the above defects. The improved BEPU method possesses the following two characteristics: (1) The sensitivity analysis is performed for the steady-state and transient calculation, respectively. It provides more comprehensive results than does the traditional BEPU method. (2) The sensitivity analysis is performed before the uncertainty analysis to reduce the number of uncertainty analysis inputs. A small-break loss-of-coolant accident (SBLOCA) is simulated by Reactor Excursion and Leak Analysis Program (RELAP) 5 to verify the accuracy and applicability of the improved BEPU method. By the sensitivity analysis, the coolant pump inlet roughness, main flow rate, core heat channel temperature, break area, and PRZ pressure have moderate or higher relationships with the peak core outlet temperature. The fission product yield factor has a moderate positive relationship with the peak cladding temperature (PCT). The sensitivity analysis by the improved BEPU method shows that the peak core outlet temperature has strong relationships with main flow rate, core heat channel temperature, and PRZ pressure, which is not captured by the traditional BEPU method. As a result, it is more reasonable to take steady-state parameters as inputs in the sensitivity analysis of transient. Only those parameters with high correlation coefficients are sampled for uncertainty analysis. Meanwhile, the results of the uncertainty analysis obtained by the improved BEPU are consistent with the results of the traditional method. Neither the PCT nor the peak core outlet temperature will exceed their limits. The results illustrate that the improved BEPU method can reduce the size of samples but maintains the desired accuracy.